Electrical and electronic waste condition and handling practices in Bangi Industrial Estate, Selangor - Roslim, Nur Fatihah; Ishak, Mohd Bakri (Integrated Publishing Association, 2011)
Due to the swift replacement of aged model by latest advanced model time to time causes short average lifespan of electrical and electronic equipment (EEE) and therefore leads to yield mass generation of waste electrical and electronic equipment (WEEE). EEE contains different hazardous materials which are harmful to human health and the environment if do not disposed carefully but E-waste is a valuable source for secondary raw materials once treated it properly. Safely recycling and discarding obsolete electronics can promote the safe management of hazardous components and supports the recovery and reuse of valuable materials. The reason is also due to the fact that the facilities are insufficiently designed to handle such kind of wastes. In addition, Malaysia is a developing country and there are many industrial areas in this country, for example Bangi Industrial Estate. Industrial area is one of a major producer of E-waste. This research seeks to study the current handling practices of WEEE in Bangi Industrial Estate, Selangor. In this research, observation, inspection and interview about E-waste handling practices was carried out in study area. Qualitative approach was used for analyzing the transcript. According to result and discussion, a quick look at it was usually enough to realize that the answers given were not transparent enough. Even though the result in terms of data was not very successful, a lot of information on the current E-waste practices was gained. Each and every factory has almost similar view in E-waste handling practices which can be stated that they obey the regulations.